2020
DOI: 10.3171/2019.6.jns19613
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid macrophage migration inhibitory factor: a potential predictor of cerebral vasospasm and clinical outcome after aneurysmal subarachnoid hemorrhage

Abstract: OBJECTIVEIn patients with aneurysmal subarachnoid hemorrhage (aSAH), poor outcomes have been shown to be correlated with subsequent cerebral vasospasm (CV) and delayed cerebral ischemia (DCI). The identification of novel biomarkers may aid in the prediction of which patients are vulnerable to developing vasospasm, cerebral ischemia, and neurological deterioration.METHODSIn this prospective clinical study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…Compared to intracerebral microdialysis, CSF analysis may reflect a more general picture of brain injury. CSF analysis basing on lumbar puncture is cornerstone for aSAH diagnosis, which means that changes of proteins can be detected quickly and conveniently to clarify the correlation between these changes and SAH pathology (Wasik et al, 2017 ; Papa et al, 2018 ; Kwan et al, 2019 ). To our knowledge, this study is the first to report the change of CSF HSP27 in patients with aSAH as compared with patients with NPH, showing a trend of increasing first and then decreasing in the early days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to intracerebral microdialysis, CSF analysis may reflect a more general picture of brain injury. CSF analysis basing on lumbar puncture is cornerstone for aSAH diagnosis, which means that changes of proteins can be detected quickly and conveniently to clarify the correlation between these changes and SAH pathology (Wasik et al, 2017 ; Papa et al, 2018 ; Kwan et al, 2019 ). To our knowledge, this study is the first to report the change of CSF HSP27 in patients with aSAH as compared with patients with NPH, showing a trend of increasing first and then decreasing in the early days.…”
Section: Discussionmentioning
confidence: 99%
“…CSF samples were collected in sterile tubes or catheter and stored at −80°C. CSF samples of patients with normal pressure hydrocephalus (NPH) were as the experimental control because CSF is difficult to obtain from healthy individuals (Kwan et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our results suggest a limited role for inflammatory cytokines in the palmitate-dependent and independent induction of Npy gene expression, and other mechanisms likely underlie this effect. While the concentrations of cytokines used in this study were somewhat higher than reported circulating or CSF concentrations in vivo (Friebe et al, 2011;Herder et al, 2008;Jain et al, 2015;Kwan et al, 2019;Niino et al, 2000;Panidis et al, 2008;von Vietinghoff & Ley, 2009), these levels are commonly used for cell line studies. Based on the efficacy of triacsin C to block the induction of Npy, palmitate metabolism appears to be an upstream mediator of the effect.…”
Section: Discussionmentioning
confidence: 80%
“…Meanwhile, peripheral circulating macrophages are recruited by monocyte chemotactic protein-1 to enter the site of injury (Lu et al, 2009;Niwa et al, 2016). Similar to microglia, monocytes and macrophages are likely to be involved in the inflammatory response or oxidative damage after SAH and lead to poor prognosis (Kwan et al, 2019;Unda et al, 2020). Therefore, further research on its mechanism will help to develop more effective treatment regimens.…”
Section: Monocytes/macrophagesmentioning
confidence: 99%